Nafas - Rashid, Zahra (Poligrafi, 2023)
For the sake of a respiratory philosophy, it makes sense to look to the East, since many Eastern traditions such as Sufism include breathwork in their so-matic practices. In my paper, I aim to show how Rumi – a 13th century Muslim theologian and Sufi – used breath or nafas in his Persian poetry to outline how breathing is an originary phenomenon. My paper will take a few samples of his poetry to demonstrate how breath connotes a newness through the “gift” of life that it endows upon us, and how the creative, endowing, and primal nature of breath is linked to an openness to the Divine other and to others. Furthermore, for Rumi, every passing breath ushers in a new existence, annihilating its older form and thus creating an ontological sense in the reader of both the finiteness of existence through what has passed and the infinite possibilities it holds when the newness arrives. Bridging the finite and infinite through breath enables us to develop a respiratory ontology that aims to conceive of dualities through an inter-related perspective. This, I wish to argue, is the true promise of Rumi’s poetry for a philosophy of breathing
Keywords: breathwork; embodied philosophy; Irigaray; Merleau-Ponty; prakse dihanja; Rumi; Sufism; sufizem; utelešena filozofija